Thank you next unpacking cancel culture on Twitter, as practiced by college students from the University of the Philippines Diliman - Vasquez, Pauline Bayani
As cancel culture became more popularized on social media, the online public became more unforgiving—one mistake and it is thank you, next. However, despite growing interest in new media studies, knowledge about it remained "surface level at best" (Haskell, 2021, p. 102).